The Development of the Lithuanian Armed Forces and Its Response to the Russian Conventional Threats in 2015‒2020 - Rogulis, Dovydas (Jaunųjų mokslininkų darbai, 2021)
In a period of 2015-2020, Lithuanian Armed Forces (LAF) military spending increased twice, thus it enabled to initiate and to arrange significant critical projects that eventually allowed armed forces to upgrade military equipment and tactics. New artillery units, armoured personnel vehicles, air defence systems, anti-tank weapons, radars, anti-drone systems boosted military power of LAF. Tactics switched from anti green men to conventional tactics, where fire and manoeuvre dominates again. Meanwhile, in the same period of time in Kaliningrad the Russian armed forces boosted the number of military personnel, upgraded equipment (most of it to offensive one) and increased military exercises. In order to be prepared, LAF must look for the most efficient ways of defence towards a potential foe. In a near future LAF must decentralize a central military storage thus critical assets could be secured and used by battalions at any time. Moreover, LAF capabilities could be improved by cyber conscripts and non-conventional tactics which could bring extra dividends when a small state fights against technologically advanced adversary. Eventually, with an additional military spending LAF could obtain MLRS artillery, the coastal defence systems and unmanned combat aerial vehicles that could deal with enemy from a safer distance.
Keywords: Lithuania; Lithuanian armed forces; Russian army; Kaliningrad; military spending; non-conventional tactics; innovations; drones; MLRS